KEMAMPUAN BERPIKIR KREATIF MAHASISWA PGSD PADA MATA KULIAH KONSEP DASAR MATEMATIKA SD - Astuti Astuti; Karlina Wong Lieung; Paustina Ngali Mahuze; St Budi Waluya; Sri Wardani; Dolince Kudiai (Program Studi PGSD Universitas Flores, 2023)
The research was conducted with the intention of analyzing students' Creative Thinking Ability (CBA) for the Elementary Mathematics Basic Concepts course. There are 3 divisions of CBA, namely high CBA, medium CBA and low CBA. The stages that the researcher has gone through are compiling a grid of questions, making questions, scoring guidelines, giving grades and categorizing the CBA. After grouping according to CBA, the students continued with determining the sample for each CBA to analyze the test results. All CBA indicators are met by high CBA student; CBA student is not yet fulfilling elaboration, sufficient in flexibility and fulfilling 2 indicators namely fluency as well as originality; and low CBA students meet the originality indicators.